International law and sustainable development : the mixed record of the MDGs and partnerships for development - (:unkn) unknown (My University, 2014)
All African countries agree that human development is a fundamental aspiration of the peoples of the region and the governments that represent them. So they all adopted the Millennium Declaration. However, overall progress has been below expectations. Between 1990 and 2000, African countries averaged only 10 per cent of the Millennium Development Goals, instead of the 40 per cent required to be on the right track. The global analysis of MDG monitoring shows that 4 countries have reached a number of specific targets and that more than one third of the countries of the subregion could reach the main objectives, particularly in the areas of schooling, nutrition, and access to clean water. Other countries, on the other hand, could face real difficulties in meeting the challenges without effective and lasting support from the international community. Despite the mixed record of partnership agreements, many experts believe that achieving the MDGs in Africa cannot be achieved without international partnerships. Hence the need to maintain the sense of realism that is to ask for the financial, technological and intellectual assistance that can bring the industrialized countries, especially those of the European Union and the United States of America , and to shift the burden of implementing the sustainable development of states towards the citizens through the dedication of "public-private" partnerships and "states / civil societies".
Keywords: African Research